2021
DOI: 10.1177/20427530211022927
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions in online higher education toward faculty mentoring

Abstract: Student persistence is important for students, faculty, and universities and online faculty mentoring supports student persistence to graduation. The online learning environment is increasingly a choice for more undergraduate students, and it continues to grow in popularity as an attractive option for adults. It is crucial to find ways to increase persistence and graduation especially given the increased use of virtual learning during the COVID-19 pandemic. Attrition rates in online learning can be high for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Mentorship can take place in any stage of life from guidance in relationships, to professional, financial, academic, and leadership advice (McWilliams & Beam, 2013). The dynamic between a mentor and a mentee is essential in shaping each upcoming generation of professionals and has been shown to benefit both the mentee, and the mentor (AuCoin & Wright, 2021;Balu & James, 2017;Evans, 2018;Lock et al, 2006;McWilliams & Beam, 2013). Some benefits of mentorship for faculty include that it provides an opportunity to improve communication skills, provides them the opportunity to practice and improve upon their teaching skills, and reflect strategies for improvement (Geesa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentorship can take place in any stage of life from guidance in relationships, to professional, financial, academic, and leadership advice (McWilliams & Beam, 2013). The dynamic between a mentor and a mentee is essential in shaping each upcoming generation of professionals and has been shown to benefit both the mentee, and the mentor (AuCoin & Wright, 2021;Balu & James, 2017;Evans, 2018;Lock et al, 2006;McWilliams & Beam, 2013). Some benefits of mentorship for faculty include that it provides an opportunity to improve communication skills, provides them the opportunity to practice and improve upon their teaching skills, and reflect strategies for improvement (Geesa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some benefits of mentorship for faculty include that it provides an opportunity to improve communication skills, provides them the opportunity to practice and improve upon their teaching skills, and reflect strategies for improvement (Geesa et al, 2020). A good faculty student mentorship program will positively affect the performance of students and faculty, which will reflect positively on the corresponding university or institution (AuCoin & Wright, 2021;McWilliams & Beam, 2013). For years, students' professional development has been a priority in higher education and a great deal of research has been conducted to find ways to improve various characteristics of student performance, progression, and success (Hammer, 2000;Lock et al, 2006;McWilliams & Beam, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting lack of intrinsic motivation and feelings of disconnect from the professor and their degree can lead students to be dissatisfied with their college experience in general and result in poor completion rates in the online environment. Online learning in general has its own set of chal-lenges due to the asynchronous nature (AuCoin & Wright, 2021), which is certainly true for e-mentoring (Mullen, 2021). Argente-Linares et al (2017) define e-mentoring "as the process in which electronic media are used as the main channel of communication between the mentor and mentee" (p. 401).…”
Section: Introductionmentioning
confidence: 99%
“…However, faculty can also assist students by guiding them into the academic community and introducing them to their own professional networks (Green, Ammah, Butler-Byrd, Brandon, & McIntosh, 2017;Almond et al, 2021). Studies have demonstrated the effectiveness of mentoring programs, either faculty-to-student or student-to-student (Nora & Crisp, 2007;Brunsma, Embrick, & Shin, 2017;Black, 2017;Baranik et al, 2017;Kutsyuruba & Godden, 2019;Almond et al, 2021;AuCoin & Wright, 2021); however, there is little agreement on a definition for mentoring, let alone straightforward best practices for institutions to adopt for e-mentoring adult learners. What is agreed upon is that mentoring is a dynamic process that involves input from both the mentor and mentee and evolves over time.…”
Section: Introductionmentioning
confidence: 99%